Transformation of Binjai Police Presence Application: UI/UX Design with Design Thinking Method to Improve Efficiency and User Experience - Algifahri, Muhammad Dzar; Putra, Donny Dwi; Zulfi, Tio Fahreza Zulfi; Lubis, Aidil Halim (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
Attendance systems have become integral to attendance management and employee supervision in various organizations. Binjai Resort Police, as a law enforcement agency in the region, is now using an access control system for all its employees. The system is expected to be a new solution for attendance management in the agency, providing efficiency and accuracy in monitoring employee attendance. In today's digital era, attention to user interface (UI/UX) is essential in product development, especially mobile applications. The ultimate goal of this study is to create an attendance mobile application prototype that meets the company's needs. Design Thinking methodology was used to focus on problem-solving by prioritizing end-user needs. The design process consists of five steps: Empathize, Define, Ideate, Prototype and Testing, and Testing. The test results show that the design is already running well, following the needs, and has the potential for further development.